Pengembangan Buku Cerita Ramayana Berbahasa Jawa sebagai Penunjang Pembelajaran Sastra Wayang Bagi Siswa Tunagrahita SMPLB di Semarang - Kirom, Dina Ashlikhatul; Mujimin, Mujimin; Widodo, Widodo (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2020)
Ramayana is a story about the Javanese puppet there in Kurikulum 2013 for Junior High School. Extraordinary Junior High School (SMPLB), specifically mental retardation, used that curriculum. The teacher of SMPLB is a classroom teacher there was find it difficult using Ramayana’s story for the lesson. Lack of teaching materials and student interest to learn Ramayana’s story make Javanese Ramayana storybook worthy to be developed. Based on the questionnaire, this Javanese Ramayana storybook is needed by teachers and students. Then generated the storybook "Crita Ramayanaku" was accorded the title and purpose of the manufactured, that used Javanese language and translated into Indonesian. From the story content, design, and image structure are feasible to use based on the assessment of media experts and materials. Then the Javanese Ramayana storybook for mental retardation students of SMPLB in Semarang proved to be effectively used in learning the story of Ramayana